Baby Ballou: A Case of an Abnormal Newborn Screen - Amy Holthouser (Association of American Medical Colleges, 2008)
Abstract Introduction This resource is a case-based team-learning session that emphasizes medical student teamwork and medical research skills to solve the puzzle of five abnormal newborn screens. Brief clinical scenarios are included as well as questions the students must research to understand the abnormal screening lab result presenting in the child. After presenting their findings to the larger group, each of four subgroups must sit down with a standardized patient playing the infant's mother and explain the significance of the abnormal lab result and need for follow-up tests and genetic counseling, if any. Standardized patient instructions are included in this case. Methods This case was developed to clinically correlate biochemistry content regarding hemoglobinopathies and thalassemias. A medical faculty member's participation is important in this case to reinforce teamwork and help the students learn how to explain complex topics to patients of average ability. This module takes place within the larger context of a 2-year interdisciplinary course for first- and second-year medical students directed by the author. Results This module is especially effective in encouraging the development of teamwork and significantly improved perceived student performance upon entry into the clinical years. It encourages a deeper understanding of basic science principles that form the basis for medical decision-making and places them in a patient-centered context. It requires clinical faculty members to spend about 2 hours with a small group of medical students or residents. Discussion Biochemistry faculty participation is welcomed but not necessary for execution of the module. The format of hemoglobin screen reporting is not user friendly and leads to confusion, even for experienced clinicians. Time during the session was spent discussing the role that confusing lab report formats play in medical errors.